FENOMENA MISTIK DIBALIK RITUAL ANNYORONG LOPI DAN DAMPAK RITUAL BAGI KETANGKASAN PERAHU PINISI DALAM PERSFEKTIF AGAMA DAN KEPERCAYAAN - Yulia, Fuspa; Fahriah, Ainul; Jusni, Jusni; Pingkiyani, Syarifah; Hasni, Hasni (Universitas Negeri Makassar, 2023)
Annyorong Lopi is a form of gratitude from boat owners and craftsmen for the completion of the boat.This research aims to find out the rituals carried out by the Bontobahari community, with the aim of uncovering the symbolic meaning, impact of the ritual, and the religious perspective that accompanies its implementation. The research methodology used is qualitative-descriptive, using a phenomenological approach. Data collection was carried out through three methods, namely interview sessions, field observations, and ritual documentation. The data was analyzed through three stages, namely data reduction, data presentation, and verification. The research results reveal that: 1) Rituals have meaning in warding off negative influences and warding off disasters, the implementation of which includes various stages that reflect gratitude for the opportunity to carry out traditions and the various values therein. 2) Rituals have a broad impact on the construction of pinisi boats, including physical, spiritual and symbolic aspects. 3)The implementation of the ritual adheres to the religious beliefs of the surrounding community. Drawing on prayers from the Quran, the ritual is conducted in accordance with Islamic teachings while preserving the cultural identity and ancestral traditions of the Bontobahari community. This ritual exemplifies the harmony between tradition, ancestral beliefs, and religion in the lives of the Bontobahari community.